On the parameters of the ion flow in a vacuum arc; Proceedings of the XXVth International Conference on Phenomena in Ionized Gases ICPIG, Nagoya, july 17-22, 2001; Vol. 3 - Mesyats G. A. Gennady Andreyevich (2001, 2001)
В фонде НТБ ТПУ отсутствует